Habitat Affects the Chemical Profile, Allelopathy, and Antioxidant Properties of Essential Oils and Phenolic Enriched Extracts of the Invasive Plant Heliotropium Curassavicum - Abd-ElGawad, Ahmed M. (Plants (Basel), 2019)
The variation in habitat has a direct effect on the plants and as a consequence, changes their content of the bioactive constituents and biological activities. The present study aimed to explore the variation in the essential oils (EOs) and phenolics of Heliotropium curassavicum collected from the coastal and inland habitats. Additionally, we determined their antioxidant and allelopathic activity against the weed, Chenopodium murale. Fifty-six compounds were identified as overall from EOs, from which 25 components were identified from the coastal sample, and 52 from the inland one. Sesquiterpenes were the main class in both samples (81.67% and 79.28%), while mono (3.99% and 7.21%) and diterpenes (2.9% and 1.77%) represented minors, respectively. Hexahydrofarnesyl acetone, (-)-caryophyllene oxide, farnesyl acetone, humulene oxide, farnesyl acetone C, and nerolidol epoxy acetate were identified as major compounds. The HPLC analysis of MeOH extracts of the two samples showed that chlorogenic acid, rutin, and propyl gallate are major compounds in the coastal sample, while vanilin, quercetin, and 4′,7-dihydroxyisoflavone are majors in the inland one. The EOs showed considerable phytotoxicity against C. murale with IC(50) value of 2.66, 0.59, and 0.70 mg mL(−1) for germination, root, and shoot growth, respectively from the inland sample. While the coastal sample attained the IC(50) values of 1.58, 0.45, and 0.66 mg mL(−1). MeOH extracts revealed stronger antioxidant activity compared to the EOs. Based on IC(50) values, the ascorbic acid revealed 3-fold of the antioxidant compared to the EO of the coastal sample and 4-fold regarding the inland sample. However, the ascorbic acid showed 3-fold of the antioxidant activity of the MeOH extracts of coastal and inland samples. Although H. curassavicum is considered as a noxious, invasive plant, the present study revealed that EO and MeOH extracts of the H. curassavicum could be considered as promising, eco-friendly, natural resources for antioxidants as well as weed control, particularly against the weed, C. murale.